Novel, Non-Radioactive, Simple and Multiplex PCR-cRFLP Methods for Genotyping Human SP-A and SP-D Marker Alleles - Susan DiAngelo (Disease Markers, 1999)
We have previously identified an allele of the human SP-A2 gene that occurs with greater frequency in an RDS population [12]. Because of the importance of SP-A in normal lung function and its newly emerging role in innate host defense and regu-lation of inflammatory processes, we wish to better characterize genotypes of both SP-A1 and SP-A2 genes. It has been determined that SP-D shares similar roles in immune response. Therefore, in this report we 1) describe a novel, non radioactive PCR based-cRFLP method for genotyping both SP-A and SP-D; 2) describe two previously unpublished biallelic polymorphisms within the SP-D gene; 3) present the partial sequence of one new SP-A1 allele (6A14) and describe other new SP-A1 and SP-A2 alleles; and 4) describe additional methodologies for SP-A genotype assessment. The ability to more accurately and efficiently genotype samples from individuals with various pulmonary diseases will facilitate population and family based association studies. Genetic poly-morphisms may be identified that partially explain individual disease susceptibility and/or treatment effectiveness.